Perceptions of Artificial Intelligence Among Healthcare Staff: A Qualitative Survey Study - Castagno, Simone; Khalifa, Mohamed (Frontiers in Artificial Intelligence, 2020)
Objectives: The medical community is in agreement that artificial intelligence (AI) will have a radical impact on patient care in the near future. The purpose of this study is to assess the awareness of AI technologies among health professionals and to investigate their perceptions towards AI applications in medicine. Design: A web-based Google Forms survey was distributed via the Royal Free London NHS Foundation Trust e-newsletter. Setting: Only staff working at the Royal Free London NHS Foundation Trust received an invitation to complete the online questionnaire. Participants: 98 healthcare professionals out of 7,538 (response rate 1.3%; confidence interval 95%; margin of error 9.64%) completed the survey, including doctors, nurses, therapists, managers and others. Primary outcome: To investigate the prior knowledge of health professionals on the subject of artificial intelligence as well as their attitudes and worries about its current and future applications. Results: 64% of respondents reported never coming across applications of AI in their work and 87% did not know the difference between machine learning and deep learning, although 50% knew at least one of the two terms. Furthermore, only 5% stated using speech recognition or transcription applications on a daily basis, while 63% never utilize them. 80% of participants believed there may be serious privacy issues associated with the use of AI and 40% considered AI to be potentially even more dangerous than nuclear weapons. However, 79% also believed AI could be useful or extremely useful in their field of work and only 10% were worried artificial intelligence will replace them at their job. Conclusions: Despite agreeing on the usefulness of artificial intelligence in the medical field, most health professionals lack a full understanding of the principles of AI and are worried about potential consequences of its widespread use in clinical practice. Without the cooperation of healthcare workers, AI tools will never be integrated into clinical practice and the NHS may miss out on an exceptionally rewarding opportunity. This highlights the need for better education and clear regulatory frameworks.